2013
DOI: 10.1109/tap.2013.2283270
|View full text |Cite
|
Sign up to set email alerts
|

A Link Loss Model for the On-Body Propagation Channel for Binaural Hearing Aids

Abstract: Binaural hearing aids communicate with each other through a wireless link for synchronization. A propagation model is needed to estimate the ear-to-ear link loss for such binaural hearing aids. The link loss is a critical parameter in a link budget to decide the sensitivity of the transceiver. In this paper, we have presented a model for the deterministic component of the ear-to-ear link loss. The model takes into account the dominant paths having most of the power of the creeping wave from the transceiver in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…This was not included in the simulation set-up, where a homogeneous head model is used. This was shown to possibly influence the measured results [5], but as shown below, it is not deemed critical here. The fill liquid in the phantom is targeted to f = 2.4 GHz and is CTIA compliant [25], with nominal electrical properties ε r,SAM = 44 and σ SAM = 2 S/m.…”
Section: A Set-upmentioning
confidence: 92%
“…This was not included in the simulation set-up, where a homogeneous head model is used. This was shown to possibly influence the measured results [5], but as shown below, it is not deemed critical here. The fill liquid in the phantom is targeted to f = 2.4 GHz and is CTIA compliant [25], with nominal electrical properties ε r,SAM = 44 and σ SAM = 2 S/m.…”
Section: A Set-upmentioning
confidence: 92%
“…7 it is seen that the radiation pattern has two lobes, which are in opposite directions. The radiation patterns for other ITE antennas found in [8,12] exhibit the same characteristic, which might indicate that this is a general trend for ITE antennas and is caused by the ear. Furthermore, it is seen that the lobe in the forward direction has the highest gain.…”
Section: Resultsmentioning
confidence: 55%
“…Therefore, contrary to BTE antennas, it is important to understand how the creeping wave propagates across the face. The previously mentioned E2E on-body path gain models in [8,9], which model the head with elliptic curves, have been tested with antennas where the main path is behind the head. Since the face is not as well modeled with elliptic curves as the back of the head, it is suggested that these models be tested with the main path around the front of the head.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the energy propagates around the body as creeping waves [9]. Furthermore, it has been shown that the E2E communication channel can be modeled as a number of elliptical paths around the head [10], [11]. In [11] an on-body radiation pattern is introduced and used to estimate the magnitude of the creeping wave launched in different directions.…”
Section: Theorymentioning
confidence: 99%